Electroporation-based technologies for medicine: principles, applications, and challenges - Yarmush, Martin L; Golberg, Alexander; Serša, Gregor; Kotnik, Tadej; Miklavčič, Damijan (Annual review of biomedical engineering, 2014)
When high-amplitude, short-duration pulsed electric fields are applied to cells and tissues, the permeability of the cell membranes and tissue is increased. This increase in permeability is currently explained by the temporary appearance of aqueous pores within the cell membrane, a phenomenon termed electroporation. During the past four decades, advances in fundamental and experimental electroporation research have allowed for the translation of electroporation-based technologies to the clinic. In this review, we describe the theory and current applications of electroporation in medicine and then discuss current challenges in electroporation research and barriers to a more extensive spread of these clinical applications.